Peruvian Journals Of This Century - Podesta, Bruno (1977)
This is a brief and first attempt of analysis and presentation of some Peruvian journals of this century; we’ll focus on culture, literature and social sciences, trying to answer, among others, the following questions: under which circumstances and with which characteristics do they appear? What position do they take against the dominant ideology? Do they adopt consciously a political posture? The important books of the Peruvian 20th century have deserved comments, exegesis and criticism; journals, in return, had a relative lower echo and, once discontinued, have passed generally to oblivion.